Culturally Relevant Information Literacy - Rob Morrison (Adult Education Research Conference, 2010)
This paper is a qualitative case study of the role of culture in the information-seeking process. This study revealed that culture does affect how we locate, evaluate and value information and thus specific kinds of knowledge. Librarians and educators must engage in discussions on “Critical Information Literacy” where information is tied to knowledge creation that does not limit learners to a specific cultural worldview. Information and information-seeking processes cannot be separated from knowledge production.